Experimental Investigation on a Fuel Efficiency and its Emission of CI Engine Using Higher Blend Biodiesel - Nik Robidin, NIk Ahmad Daniel; Shaiful Fadzil Zainal Abidin (Progress in Engineering Application and Technology, 2024)
Biodiesel fuel reduces greenhouse gas emissions and dependence on fossil fuels, making it an environmentally friendly choice for powering vehicles and industrial engines. Determining the optimal biodiesel blending ratio is vital for maximizing engine performance and minimizing environmental impact, ensuring a balanced approach to sustainable energy use. This study aims to evaluate the fuel consumption and emission of a compressed ignition engine with various blending ratios. The research outputs will examine its brake-specific fuel consumption (BSFC) and emission level. The methodology consists of a set of precise experiments carried out on a testing engine. The experiments involve systematically altering the blend ratios of biodiesel and analysing their impact on the efficiency of combustion and emissions. The engine’s fuel consumption and exhaust emissions is measured extensively under different operating conditions, allowing for a comprehensive evaluation. The experiment reveals when the percentage of biodiesel blends increases, fuel efficiency slightly decreases as the fuel’s overall energy content lowered and engine performance decreased. This suggests that biodiesel gives somewhat less energy for a given amount. This finding is valuable and will contribute to the development of sustainable and efficient fuel strategies. The pressing need for eco-friendly transportation solutions motivates this investigation to offer viable alternatives in renewable energy sources and cleaner propulsion technologies.